A Method for Rapid Virtual Assembly Generation from Physical Devices. Issue 4 (February 2020) - Lin, Chen; Wang, Jianxing; Lin, Hong; Lin, Xiaobin
Abstract: The creation of virtual assembly models for these devices would be a valuable supplement for the purpose of education. To reduce the time and human resources in the creation of virtual assembly models, this paper presents a rapid virtual assembly generation method based on physical devices, which employs a 3D scanner for raw 3D data acquisition, GEOMAGIC DESIGN X, ANARK CORE WORKSTATION and VIZARD as software tools for the creation of virtual assembly interaction. The experimental results show that this method can rapidly visualize physical devices, shorten development cycle and reduce development time and cost.